STRATEGI PENGEMBANGAN DESA WISATA BENGKEL, TABANAN - Novera, Suci; Sudiarta, I Nyoman; Wijaya, NMS. (Jurnal IPTA (Industri Perjalanan Wisata), 2025)
Bengkel Village is one of the pilot tourism villages in Tabanan Regency with potential in natural, cultural, and man-made tourism attractions, making it highly suitable for development. This research aims to assess the internal and external conditions of Bengkel Tourism Village and propose strategies for its sustainable tourism development in Tabanan Regency. Data collection methods include observation, in-depth interviews, documentation, and literature review. The study utilizes the AFITH concept (Attraction, Facilities, Infrastructure, Transportation, and Hospitality) and PEST analysis (Political, Economic, Social, and Technological). Informants were selected using purposive sampling, comprising key informants, primary informants, and additional informants. The findings identify four strategic points for Bengkel Tourism Village development: attraction and tourism destination enhancement strategy, comprehensive tourism program strategy, quality improvement strategy, and human resources development strategy.